2007
DOI: 10.1007/s10584-007-9278-8
|View full text |Cite
|
Sign up to set email alerts
|

High resolution modeling of the regional impacts of climate change on irrigation water demand

Abstract: In the Arkansas River Basin in southeastern Colorado, surface irrigation provides most of the water required for agriculture. Consequently, the region's future could be significantly affected if climate change impacts the amount of water available for irrigation. A methodology to model the expected impacts of climate change on irrigation water demand in the region is described. The Integrated Decision Support Consumptive Use model, which accounts for spatial and temporal variability in evapotranspiration and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…However, the information on the future irrigation requirements of viticulture and the magnitude of other related risks (salinity) in the soil is sparse. A number of modeling studies have attempted to evaluate the effects of climate change on water use in agriculture for other crops (Fischer et al, 2007;Elgaali et al, 2007;De Silva et al, 2007;Xiong et al, 2010;Gondim et al, 2012;Save et al, 2012;Lee and Huang, 2014;Woznicki et al, 2015). Most of these studies showed an increase in the irrigation demand for typical annual crops.…”
Section: Introductionmentioning
confidence: 99%
“…However, the information on the future irrigation requirements of viticulture and the magnitude of other related risks (salinity) in the soil is sparse. A number of modeling studies have attempted to evaluate the effects of climate change on water use in agriculture for other crops (Fischer et al, 2007;Elgaali et al, 2007;De Silva et al, 2007;Xiong et al, 2010;Gondim et al, 2012;Save et al, 2012;Lee and Huang, 2014;Woznicki et al, 2015). Most of these studies showed an increase in the irrigation demand for typical annual crops.…”
Section: Introductionmentioning
confidence: 99%
“…A number of works have been carried out to study the impact of climate change on irrigation water demand (Fischer et al 2006;Elgaali et al 2007;Yano et al 2007a;Rodriguez Diaz et al 2007;de Silva et al 2007). Elgaali et al (2007) modeled the regional impact of climate change on irrigation water demand in the Arkansas River Basin in southeastern Colorado.…”
Section: Introductionmentioning
confidence: 99%
“…Elgaali et al (2007) modeled the regional impact of climate change on irrigation water demand in the Arkansas River Basin in southeastern Colorado. They assumed no change in crop phenology and found an overall increase in irrigation water demands due to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The review of published data of climate change impact on IWD reveals large variation between crops and growing regions [27][28][29][30][31][32][33][34]. A global statement about climate change impact on agriculture is not possible and the insights gained cannot simply be assigned from one crop or region to another.…”
Section: Introductionmentioning
confidence: 99%